Contribution of vertical and horizontal components of ground reaction forces on global motor moment during a golf swing: a preliminary study - Bourgain, M.; Sauret, C.; Rouillon, O.; Thoreux, P.; Rouch, P. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
The swing is a crucial movement for golf performance. During their swing, golfers apply forces on the ground through their feet at the origin of the clubhead acceleration. Most of the studies that investigated ground reaction forces during a golf swing focused on the vertical component. However horizontal forces (mediolateral and anteroposterior components) were shown to be different between golfers and to play a role in the generation of the global moment creating the clubhead acceleration (McNitt-Gray et al. 2013).